2002
DOI: 10.1590/s0100-879x2002001000006
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic determination of goiter prevalence in southern Brazilian schoolchildren

Abstract: The aim of the present study was to estimate the prevalence of goiter in schoolchildren in a formerly iodine-deficient region in southern Brazil by assessing the relationship between body surface area (m 2 ) and thyroid volume (ml) measured by ultrasonography. A populationbased sample of 1,094 randomly selected schoolchildren (6 to 14 years; 556 boys and 538 girls) underwent clinical evaluation. A total of 119 (10.9%) children were diagnosed with goiter upon clinical examination according to WHO criteria (grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Accordingly, the higher odds of having goiter were noted among children from households using the unprotected source of water. The finding was in agreement with the previous studies of other developing countries [10, 4345], in which contamination of drinking water with Coliforms and E. Coli contributes to the development of goiter. The current study revealed that the majority, (96.6%), of the households did not treat water to make it safer for consumption.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, the higher odds of having goiter were noted among children from households using the unprotected source of water. The finding was in agreement with the previous studies of other developing countries [10, 4345], in which contamination of drinking water with Coliforms and E. Coli contributes to the development of goiter. The current study revealed that the majority, (96.6%), of the households did not treat water to make it safer for consumption.…”
Section: Discussionsupporting
confidence: 93%
“…It was documented that, poor maternal knowledge towards iodized salt use was positively associated with goiter [32, 40, 45]. Similarly, the odds of having goiter were reduced by 35% among children whose mothers had medium knowledge compared to those children whose mothers had poor knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…yroid gland ultrasonography is a more precise method than palpation technique for determining thyroid volume and has been recommended as the standard criterion in epidemiological surveys [17]. Urinary iodine concentration is a well-accepted, cost-effective, and easily obtainable indicator for iodine status [15].…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is a country of high ethnic admixture, allowing examination of the influence of demographics and other risk factors on hypothyroidism. However, thyroid function tests in Brazil have been limited to specialized clinical settings and most Brazilians are unaware of their TSH levels, 7 with most Brazilian studies being related to goitre prevalence in schoolchildren 8–10 . We evaluated the risk factors associated with hypothyroidism in Brazilian women, particularly testing whether environmental factors could explain the relationship between hypothyroidism and race.…”
Section: Introductionmentioning
confidence: 99%